Incidence of Bile Duct Injury after Laparoscopic Cholecystectomy at Combined Military Hospital Rawalpindi - Awais, Saqib Ali; Malik, Arslan Sharif; Ahmad, Iftkhar; Niazi, Javed Iqbal; Soomro, Jehangir Ali; Mehmood, Hassan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the incidence and risk factors of bile duct injury after laparoscopic cholecystectomy.Study Design: Prospective cross-sectional study.Place and Duration of Study: Combined Military hospital, Rawalpindi Pakistan, from Jan to Nov 2022.Methodology: All patients with age 18 to 70 years of either gender undergoing laparoscopic cholecystectomy were followed for 30 days. Common bile duct injuries were defined based on the Strasberg-Bismuth classification. Injuries following laparoscopic cholecystectomy are categorized using the McMahon categorization system as either major or minor, depending on their severity.Results: Of 962 patients, the incidence of bile duct injury was observed in 8(0.8%) patients. A statistically significant association of incidence of bile duct injury was observed with cholecystitis (p-value 0.029), renal disease (p-value 0.038), and obesity (p-value 0.026). Of 8 patients with bile duct injury, obesity was found in all, i.e., 8(100%). Most of the bile duct injuries were diagnosed postoperatively, i.e., 6(75.0%) whereas 2(25.0%) were diagnosed intraoperatively. Half of the patients with CBD injury had Type A Strasberg-Bismuth injury, i.e., 4(50.0%), 2(25.0%) had type D, whereas 1(12.5%) had type E1 and type E5 each. While McMahon classification report that 5(62.5%) had a minor depth of injury whereas 3(3.4%) had a major depth of injury.Conclusion: Incidence of laparoscopic cholecystectomy was observed in less than 1% of the patients. Patients with cholecystitis, renal disease, and obesity are at-risk. Type A Strasberg-Bismuth injury was found in majority of the patients.